2022
DOI: 10.21203/rs.3.rs-1287331/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paradigm shift in understanding the Galactic eROSITA Bubbles

Abstract: The magnificent bubbles at the Galactic center provide a great channel to understand the effects of feedback on galaxy evolution. The newly discovered eROSITA bubbles show enhanced X-ray emission from the shells around bubbles. Previous works assumed that the X-ray emitting gas in the shells has a single temperature component and that they trace the shock-heated lower-temperature Galactic halo gas. Here we show that the thermal structure of the eROSITA bubble shells is more complex. Using Suzaku observations… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The same was found by Das et al (2021) for Mrk 421, whose line of sight does not cross the bubbles. This is further confirmed by emission studies of the CGM, which have found a hot component coexistent with the virial phase toward directions away from the Galactic center (e.g., Bhattacharyya et al 2022;Bluem et al 2022;Gupta et al 2022).…”
Section: The Extended Hot Cgm Componentmentioning
confidence: 55%
See 1 more Smart Citation
“…The same was found by Das et al (2021) for Mrk 421, whose line of sight does not cross the bubbles. This is further confirmed by emission studies of the CGM, which have found a hot component coexistent with the virial phase toward directions away from the Galactic center (e.g., Bhattacharyya et al 2022;Bluem et al 2022;Gupta et al 2022).…”
Section: The Extended Hot Cgm Componentmentioning
confidence: 55%
“…However, our analysis is too limited to further explore this possibility. This result would be in contrast to the emission measure of the CGM hot and warm phases, which have been observed to vary by an order of magnitude in large and short scales (Das et al 2019;Gupta et al 2021Gupta et al , 2022Bhattacharyya et al 2022;Bluem et al 2022).…”
Section: Spatial Distribution Of the Hot Phase Of The Cgmmentioning
confidence: 65%